Elabela levels in pregnancies with intrauterine growth retardation - Yener, Gulen; Kavak, Salih Burcin; Gul, Yeliz; Kavak, Ebru Celik; Bulmus, Funda Gulcu; Sanli, Cengiz; Bulu, Gulay (Via Medica, 2023)
Objectives: The aim of our study is to examine maternal serum Elabela levels in pregnancy with intrauterine growth retardation (IUGR). IUGR is one of the most important causes of perinatal mortality and morbidity. IUGR is also related future comorobidities such as diabetes mellitus, hyperlipidemia, hypertension and coronary artery disease.Material and methods: Fifty pregnancies diagnosed as IUGR (Group 1) and fifty healthy pregnancies (Group 2) enrolled into the study. Obstetric and demographic characteristics of the patients, serum elabela levels, ultrasound parameters, cord pH value and APGAR scores of the newborns were recorded. In the study, which was planned as a prospective case-control study, an independent t test was used for the evaluation of continuous data and the Mann Whitney U test was used for the statistical evaluation of ordinal data. p < 0.05 was considered significant.Results: The mean gestational age of the cases at delivery was 36.35 +/- 1.29 in Group 1 and 38.16 +/- 0.94 weeks in Group 2 (p < 0.05). Mean serum Elabela levels were 15.05 +/- 9.03 in Group 1 and 8.96 +/- 4.33 ng/mL in Group 2 (p < 0.0001). Mean newborn weights were 2498.20 +/- 465.92 in Group 1 and 3179.44 +/- 387.99 gr. in Group 2 (p < 0.0001). Systolic and diastolic blood pressure measurements taken on the day of delivery were higher in Group 1, and diastolic blood pressure was 77.0 +/- 9.53 in Group 1 and 72.60 +/- 13.37 mmHg in Group 2 (p < 0.05). Bilateral uterine artery Pulsatile Index (PI) and umbilical artery PI value were significantly higher in Group 1 (p < 0.05), and middle cerebral artery PI and cerebroplacental ratio were significantly lower in Group 1 compared to Group 2 (p < 0.05). Although the cord pH value, 1st and 5th minute APGAR scores were lower in Group 1 compared to Group 2, no statistically significant difference was found (p > 0.05).Conlusions: In our study, it was found that serum Elabela levels increased significantly in pregnancies complicated by IUGR compared to the control group.
Keywords: pregnancy; intrauterine growth retardation; Elabela